Chasing the high-resolution mapping of rotational and strain FRFs as receptance processing from different full-field optical measuring technologies. (1st March 2022) - Zanarini, Alessandro
Abstract: Thanks to the recent advances in digital vision systems, a question might arise about where the full-field optical and contactless methods can bring modern design procedures. An answer lies on the methodologically detailed comparison of the results, processed from different full-field optical techniques, in exploring consistent and high-resolution maps of rotational and strain FRFs that is done through this paper. Great exertions were first put in thoroughly testing a thin aluminium plate, in its real dynamics as a lightweight structure with broad frequency band dynamics and high modal density, in a unique comparative set-up, to obtain Receptance FRF maps of displacements-over-force by means of 3 different full-field optical techniques (SLDV, DIC, ESPI). There resulted superior quality Receptance maps in a broad and dense frequency domain, with high-resolution and continuity-wise consistent mapping at each frequency line. This paper exploits the here detailed robust numerical differentiation and signal processing in order to calculate the Impedance -based models of rotational and strain FRFs . Especially for DIC and for ESPI, both rarely used on many frequency lines, the fully populated FRFs for rotations and strains are a clear novelty, with rotational Coherence functions as added quality assessment features. The systematic comparison of the results obtained in the same location of the sample, by means of spatial and frequency domain metrics, is possible because of the proposed pointwise procedure, permitting the first numerical matching assessment of the 3 optical technologies on these awaited experiment-based quantities, as the full-field rotational and strain FRFs .